Ambientalização da gestão universitária: um olhar sobre a Universidade Federal da Paraíba - Xavier Júnior, José Rômulo Batista (2024)
A growing body of scientific evidence attests that the Earth's suffering from the unchecked exploitation of Its resources. Brazilian public universities, as pillars of higher education, assume a crucial role in forming conscious citizens and promoting social progress. Their mission extends beyond academic instruction to include the construction of knowledge and the fostering of socio-environmental development at various scales. In this context, it becomes imperative for universities to assume an ethical, scientific, and political commitment to addressing the socio-environmental crisis, a challenge that permeates all aspects of contemporary society. Given this, this dissertation aims to analyze the process of environmentalization in the Institutional Management Policy of the Federal University of Paraíba between 2013 and 2023. To achieve this, it discusses the relevance of anthropogenic action and the capitalist mode of production in the global environmental crisis through the concepts of the Anthropocene and Capitalocene. It also seeks to clarify the meaning of the much-discussed environmental crisis, exposing the idea of planetary boundaries and the consequences of exceeding these thresholds. Having established this context, the sociological notion of environmentalization is addressed. This allows the introduction of the concept of environmentalization in higher education, which is the process by which socio-environmental themes are integrated into curricular content and practices (teaching) in a manner integrated with other instances of the university educational process (research, extension, and management). The literature on environmentalization in each of the spheres of higher education, with an emphasis on the management dimension, is then addressed in detail. This entire described path is composed of preparatory steps necessary for the effective achievement of the research objectives, since, as this is a bibliographic and documentary research, these debates make it possible to justify in a well-founded manner the choices made for the formation of the body of documents to be analyzed in the research. Finally, the selected documents are used to describe, understand, and discuss the environmentalization process in the institutional management policy of the Federal University of Paraíba. This is done through a description of the institutional organization of the units that act for this purpose and through a detailed discussion of the results obtained by the institution in the international platform UI GreenMetric World University Ranking, 2023 edition. In terms of methodology, the research adopts a qualitative approach, with the adoption of the deductive logical procedure, which allows starting the research from the study of a general reality and gradually narrowing the universe of analysis to specific themes and social realities. The Technical-Technological Product of the Research consists of a proposal for an institutional program whose main objectives are the elaboration of a participatory master plan that foresees the adoption of sustainability practices in areas such as water, energy, and waste; and the updating of the institution's Sustainable Logistics Plan, so that the institution can comply with the requirements established in Ordinance Seges/ME No. 8.678, of July 19, 2021, regarding the implementation of governance instruments in the contracts carried out by the Federal University of Paraíba.